PERAN ADMINISTRATOR KESEHATAN YANG EFEKTIF - Asni Zahara; Wasiyem; Nanda Fadillah Darus; Supangge Tiara Aulia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
A health administrator is a very important person in the health field. A health administrator is a person who is responsible for planning, organizing, leading, and controlling resources in a health institution. The purpose of this research is to find out the role of leadership and health administrators. The data collection techniques in this study using library research where researchers collect data by reading, studying, and analyzing journals, books articles from previous researchers. According to the results of the research, it can be concluded that health administrators have a crucial role in maintaining performance and efficient use of resources in the health system through good management, effective cooperation, and the use of decision making.